Combination of Spiritual Benson Relaxation and Lavender Aromatherapy (SBR-LA) on Anxiety, Sleep Quality and Blood Pressure in Hypertension Patients - Muhammad Basuni; Eppy Setiyowati; Chilyatiz Zahroh (Journal of Nursing Practice)
Background: A person's anxiety due to an illness is one of the causes of hypertension or an increase in blood pressure above the normal limit in all age groups. Hypertension that is not recognized and is not treated immediately can cause various kinds of comorbidities. Therefore, apart from pharmacological treatment, non-pharmacological therapy is also needed to reduce anxiety and blood pressure and improve the quality of sleep for hypertension sufferers.